Analysis of the Functional Relevance of Epigenetic Chromatin Marks in the First Intron Associated with Specific Gene Expression Patterns. (8th February 2019) - Jo, Shin-Sang; Choi, Sun Shim
Abstract: We previously showed that the first intron of genes exhibits several interesting characteristics not seen in other introns: 1) it is the longest intron on average in almost all eukaryotes, 2) it presents the highest number of conserved sites, and 3) it exhibits the highest density of regulatory chromatin marks. Here, we expand on our previous study by integrating various multiomics data, leading to further evidence supporting the functionality of sites in the first intron. We first show that trait-associated single-nucleotide polymorphisms (TASs) are significantly enriched in the first intron. We also show that within the first intron, the density of epigenetic chromatin signals is higher near TASs than in distant regions. Furthermore, the distribution of several chromatin regulatory marks is investigated in relation to gene expression specificity (i.e., housekeeping vs. tissue-specific expression), essentiality (essential genes vs. nonessential genes), and levels of gene expression; housekeeping genes or essential genes contain greater proportions of active chromatin marks than tissue-specific genes or nonessential genes, and highly expressed genes exhibit a greater density of chromatin regulatory marks than genes with low expression. Moreover, we observe that genes carrying multiple first-intron TASs interact with each other within a large protein–protein interaction network, ultimately connecting to the UBC protein, a well-established protein involved in ubiquitination. We believe that our results shed light on the functionality of first introns as a genomic entity involved in gene expression regulation.